What AI “art” can teach us about art - Simona Chiodo (Journal of Aesthetics & Culture)
In the last years, the use of the words “AI art”, i.e. art produced by artificial intelligence, has exponentially increased. Sometimes, they have been used without philosophical awareness, from public discourse to strictly scientific and technological literature. Sometimes, they have started entering the philosophical debate, from the philosophy of technology to the philosophy of art. In what follows, I shall reflect upon AI art by combining my expertise in both the philosophy of technology and the philosophy of art as what has characterised my work as a philosopher over the years. More precisely, I shall reflect upon AI art as an opportunity to further question what we mean when we use the word “art”. After a brief literature review (first section), I shall specify what kind of AI art I consider (second section). In the third section, I shall analyse the most important reason why AI artefacts are defined as art. In the fourth and fifth sections, I shall use thought experiments to argue that AI artefacts cannot be defined as art. And, in the sixth section, I shall conclude by questioning what the use of the words “AI art” can show us about both art and our technological era.